Pregnancy in the Obese Woman : Clinical Management - Conway, Deborah L. (Chichester, West Sussex, UK : Wiley-Blackwell, 2011)
Obesity is becoming an increasing global healthcare challenge, and overweight expecting mothers are at risk of complications during their pregnancy. This unique clinical focused book covers evidence-based practices for obstetricians and assists them as they care for both the fetus as well as the mother-to-be if a critical circumstance develops during the pregnancy.
The epidemiology of obesity in pregnancy / Susan Y. Chu -- Psychological aspects of obesity in women / Yvette Lacoursiere -- Preparing for pregnancy : special considerations for the obese woman / Anne Lang Dunlop, Divya Narayan, and Vita Lam -- Bariatric surgery : a primer for the obstetric care provider / C.R. Hall and Bradley J. Needleman -- Pregnancy after bariatric surgery / Anatte Karmon and Eyal Sheiner -- The impact of maternal obesity on fetal and neonatal outcomes / Donald J. Dudley -- Abnormal fetal growth related to maternal obesity / Hugh M. Ehrenberg -- Special considerations in prenatal care / Hugh M. Ehrenberg -- Nutrition and weight gain in the obese gravida / Naomi E. Stotland, Janet King, and Barbara Abrams -- Exercise recommendations for the obese gravida / Krista L Rompolski and John M. Jakicic -- Obesity co-morbid conditions in pregnancy : diabetes and hypertension / Eran Hadar and Yariv Yogev -- Obstetric management of the obese parturient / James M. Alexander -- Operative techniques for abdominal surgery in the morbidly obese patient / Ashley Parker and Deborah L. Conway -- Breast feeding and contraception : special considerations in obese women / Elizabeth Reifsnider.
Includes bibliographical references and index.
Print version record.
Keywords: Obesity; Pregnancy -- Complications; Obesity; Pregnancy Complications; Pregnancy Outcome; Pregnancy, High-Risk.; Risk Factors; Medicine; HEALTH & FITNESS -- Pregnancy & Childbirth; Obesity; Pregnancy -- Complications; Electronic books